Degradation potential of different lignocellulosic residues by Trichoderma longibrachiatum and Trichoderma afroharzianum under solid state fermentation. (January 2022) - Li, Wanyun; Zhao, Lili; He, Xueli
Graphical abstract: Highlights: Two Trichoderma strains were isolated from the rhizospheric soil of medicinal plants. Fermentation factors of lignocellulosic residues by Trichoderma strains was assessed. Substrate components was a crucial factor affecting fermentation results. T. afroharzianum showed pronounced cellulose degradation efficiency for corn straw. Two Trichoderma strains would be useful for application in waste materials treatment. Abstract: To achieve an economically viable substitutive strategy for lignocellulosic residues use, cellulose degradation by efficient Trichoderma strains become a key alternative. This study aimed to explore the effects of various cultural conditions on the degradation of different lignocellulosic substrates (corn straw and licorice residues) by Trichoderma longibrachiatum and Trichoderma afroharzianum in solid state fermentation. The strains were isolated from the rhizospheric soils of medicinal plants. In addition, the best fermentation combination was selected to evaluate the degradation results. This study confirmed that fermentation conditions and different components of corn straw and licorice residues were both crucial factors affecting the cellulase activity and spore production of two Trichoderma strains. A combination of T. afroharzianum degrading corn straw was selected for Response Surface Methodology optimization. The best fermentation conditions were fermentation time of 5.72 days, initial material liquid ratio of 1:4.58, initial pH of 6.32 and fermentation temperature of 28.8 ℃, with a filter paper cellulase activity of 0.91 U/mL. After continuous fermentation, the spore production reached 6.18 × 10 9 spores/g, the crude fiber degradation rate reached 23.5 % with the reducing sugar content maintained at 11 mg/g. These results highlight the great potential of T. afroharzianum degrading corn straw for organic amendment.